The effect of Project-Based Learning on Technological Pedagogical Content Knowledge among Elementary School Pre-Service Teacher - Erviana, V.Y. (Pegem Akademi Yayincilik Egitim Danismanlik Hizmetleri Ticaret A.S., 2022)
The ability to integrate technology in learning, also known as Technological Pedagogical Content Knowledge (TPCK), is one of the competencies that teachers must master in the era of the Industrial Revolution 4.0. TPCK can be prepared when a teacher becomes a pre-service teacher at a university. The goal of this study was to describe the impact of Project-Based Learning (PjBL) on TPCK in elementary school pre-service teachers. This research is an experimental study with a one-group pretest-posttest design. A total of 94 pre-service elementary school teachers are included in this studyâs sample. Data collection instruments to measure TPCK are questionnaires and assessment sheets. The questionnaire was used to measure TK, PK, CK, TCK, PCK, and TPK. The assessment is used to measure TPCK. TPCK is assessed using the outcomes of student-created learning materials. The data is analyzed using descriptive statistics and inferential statistics. To describe the distribution of TPCK data, descriptive statistics are used. To test the study hypotheses, inferential statistics are used. The paired sample t-test was used to test the hypothesis. The descriptive analysis results suggest that the TPCK for pre-service teachers is in the high range. The results of hypothesis testing show a significant effect of using PjBL on TPCK of pre-service elementary school teachers. These findings highlighted PjBLâs potential for TPCK development. Â© 2022